Seasonal changes in plasma concentrations of the thyroid, glucocorticoid and reproductive hormones in the tegu lizard Salvator merianae - Zena, Lucas A.; Dillon, Danielle; Hunt, Kathleen E.; Navas, Carlos A.; Bícego, Kênia C.; Buck, C. Loren (General and comparative endocrinology, 2019)
•Higher sex, adrenal and thyroid hormones levels in active than hibernation season.•Testosterone and estradiol peaks coincide in September, during reproductive season.•Progesterone in females peaks a month later than estradiol.•Seasonal changes of corticosterone suggest a role in mobilization of energy stores.•Spring T3 surge occurs only in females; high energy investment in reproduction. The tegu lizard Salvator merianae is a large, widely distributed teiid lizard endemic to South America that exhibits annual cycles of high activity during the spring and summer, and hibernation during winter. This pattern of activity and hibernation is accompanied by profound seasonal changes in physiology and behavior, including endothermy during the austral spring. The unusual combination of seasonal endothermy, hibernation and oviparity, in a non-avian, non-mammalian species, makes S. merianae an interesting subject for study of comparative aspects of endocrine regulation of seasonal changes in physiology. In the present study, we first validated commercially available immunoassay kits for quantification of hormone concentrations of the reproductive (testosterone, estradiol and progesterone), adrenal (corticosterone), and thyroid [thyroxine (T4) and triiodothyronine (T3)] axes in plasma of an outdoor, captive adult male and female S. merianae in southeastern Brazil. All assays exhibited parallelism and accuracy with S. merianae plasma. We next assessed patterns of concentration of these hormones across the annual cycle of S. merianae. Testosterone in males and estradiol in females peaked in spring coincident with the peak in reproductive behavior. Progesterone in females was significantly elevated in October coincident with putative ovulation when gravid females build nests. Thyroid hormones, known for regulating energy metabolism, varied seasonally with some sex-dependent differences. T4 gradually increased from an annual nadir during pre-hibernation and hibernation to high concentrations during spring in both sexes. In contrast, T3 did not vary seasonally in males, but females showed a two-fold increase in T3 during the spring reproductive season. T3 may be involved in energy investment during the seasonal production of large clutches of eggs. Corticosterone was significantly elevated during the active season in both sexes, suggesting its involvement in mobilization of energy stores and modulation of behavior (territoriality) and physiology. Ours is the first investigation of concurrent changes in reproductive, thyroid and adrenal hormone concentrations in this endemic and physiologically unique South American lizard. Our findings set the stage for future investigations to determine the extent to which these hormones influence activity and thermoregulation in S. merianae.